Futsal Passing Training Model Based on Audio Visual Media - Iqbal Pranata; Hidayat, Arif; Noviria Sukmawakti; Selvi Melianty (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
This study aims to know, identify and analyze the "Futsal Passing Practice Model Based on Audio Visual Media in Class X Students at SMK N 5 Palembang". This study uses the Borg & Gall method. Based on the results of calculations in small and large group trials that have been validated and evaluated by the three experts, the category of "Very Good" was obtained. In the small group trial, 84.95% while in the large group trial, a percentage of 91.6% was obtained, which can be seen by the increase in the percentage before the product revision and after the product revision. This shows that the feasibility level of the implementation of the development of a passing futsal training model based on audio visual media has been significantly improved for the subjects studied, namely in futsal extracurricular students of SMK Negeri 5 Palembang.